Case Report: Anlotinib for advanced chordoma - Jing, Zhining; Song, Chunmiao; Jiang, Yongqiang (Frontiers in Oncology, 2026)
Chordoma is a rare tumor with low to moderate malignancy. It is typically treated with surgical resection in the early stages. However, due to the slow growth and locally invasive biological characteristics of chordoma, patients are often diagnosed at an advanced stage, rendering them ineligible for surgery. This case report describes a 71-year-old male patient who experienced notable symptom relief after receiving single-agent anlotinib treatment for advanced thoracic chordoma. According to the World Health Organization (WHO) criteria for solid tumors, imaging examinations indicated that the patient achieved a partial response (PR). These findings suggest that anlotinib has potential therapeutic value in the treatment of chordoma, primarily in managing symptoms and tumor progression. In this report, we retrospectively analyzed the patient’s case data and discussed it in conjunction with relevant literature to provide new therapeutic strategies for clinicians facing similar patients.